Producción de sandia (Citrullus lanatus) con dos sistemas de tutoreo en el Centro Experimental La Playita de la Universidad Técnica De Cotopaxi extensión La Maná 2015 - Peñarrieta Olvera, Lucia Mabel (2015)
This research was conducted at the Center Experimental "La Playita" geographical WGS 84 Length SO ° 56.57 "; length w 17 13 "25. The objectives were to evaluate the production of watermelon (Citrullus lanatus) by applying two sets of tutoring, to determine the production of watermelon in the Experimental Center La Playita, and how best tutoring system for the production of watermelon. The experimental design was use is completely randomized design (CRD) with two tutoring systems, plus a control and four experimental units per treatment....